Radiological progression of hip osteoarthritis: definition, risk factors and correlations with clinical status. Issue 6 (June 1996) - Dougados, M; Gueguen, A; Nguyen, M; Berdah, L; Lequesne, M; Mazieres, B; Vignon, E
Abstract : OBJECTIVES: To determine a cut off value for changes in radiological joint space width that allowed definition of radiological progression of hip osteoarthritis not related to measurement method errors and, thereafter, to determine factors predictive of radiological progression of hip osteoarthritis and to evaluate the correlations between clinical and radiological parameters. METHODS: A prospective, longitudinal (one year duration), multicentre study was made of patients with osteoarthritis of the hip (American College of Rheumatology criteria). Data on clinical activity (pain, functional impairment), demographic data (age, gender, body mass index), and femoral head migration (superolateral, superomedial, concentric) were collected when the patient entered the study; radiological grade (joint space width in millimetres at the narrowest point using a 0.1 mm graduated magnifying glass, evaluated by a single observer unaware of the chronology of the films) was recorded at the patient's entry to the study and after one year. RESULTS: Analysis of the means of the differences between two analyses performed by a single observer of 30 pairs of radiographs (one performed after an interval of one year) (0.06 (SD 0.23)) suggested that a change of more than 0.56 mm (2 SD) after a one year follow up could define progression of osteoarthritis of the hip. Of the 508 patients recruited, 461 (91%) completed the one year follow up and radiological progression was observed in 102 (22%). The factors predictive of radiological progression that were identified in the multivariate analysis were: radiological joint space width at entry < or = 2 mm, superolateral migration of the femoral head, female gender, Lequesne's functional index > 10, age at entry > 65 years (odds ratios 2.11, 4.25, 2.51, 2.66, 1.90, respectively). The level of clinical parameters (pain, functional impairment) and the amount of symptomatic treatment required (non-steroidal anti-inflammatory drugs and analgesic intake) accounted for 20% (p < 0.0001) of the variability of the changes in radiological joint space width over the one year study period. CONCLUSION: These data suggest that radiological progression of hip osteoarthritis could be defined by a change in joint space width of at least 0.6 mm after a one year follow up period, is correlated with the changes in clinical status of the patients, and is related not only to demographic data (age, gender), but also to some specific characteristics of osteoarthritis (localisation, radiological severity, clinical activity).